Navigating peer bullying: parents’ and students’ communication patterns, behavioral responses, and coping strategies - Najmi Hayati; Mohd Khairi Ismail; Nur Adyani Sabarudin; Nor Aziyatul Izni (Intelektual Pustaka Media Utama, 2026)
This study examined how bullying experiences influence adolescents’ coping strategies, with a particular focus on parent-student communication as a predictor of coping outcomes. Using a mixed-methods approach in Indonesia, data were collected from 78 secondary school students through surveys measuring bullying exposure, communication patterns, and coping strategies, complemented by in-depth interviews with four parent-student pairs. Quantitative analysis using descriptive statistics and Pearson correlation coefficients showed that higher levels of bullying were significantly associated with poorer communication with parents and reduced use of problem-focused coping strategies, while bullying was positively correlated with emotion-focused and maladaptive coping. Qualitative findings supported these results and revealed four key themes: experiences of bullying, communication patterns, emotional responses, and coping mechanisms. Parental involvement, particularly in providing emotional support and engaging in joint problem-solving, emerged as a critical protective factor. The novelty of this study lies in demonstrating the central role of parent-student communication in shaping adolescents’ coping responses to bullying. Overall, the findings suggest that strengthening family communication through targeted interventions may reduce adolescents’ reliance on maladaptive coping strategies and promote more effective, problem-focused approaches to managing bullying experiences.